Microporous hybrix mulching material comprising graphene oxide and method for manufacturing the same
The microporous hybrid mulching material addresses issues of aeration and durability in conventional materials by using a laminated structure with graphene oxide and titanium dioxide for improved soil respiration and light reflection, enhancing crop growth and yield.
Patent Information
- Application Number
- KR1020260035323
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-02-26
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2046-02-26
AI Technical Summary
Conventional mulching materials face issues such as reduced aeration leading to soil waterlogging and disease outbreaks, lack of durability causing frequent replacement and waste generation, and uneven light supply affecting crop growth and productivity.
A microporous hybrid mulching material with a laminated structure comprising a white microporous film and a black nonwoven fabric, incorporating graphene oxide, calcium carbonate, and titanium dioxide for improved breathability, thermal conductivity, and optimized light reflection, along with perforated holes for air circulation and hydrophilic surfactant impregnation.
Enhances crop growth by promoting root respiration, reducing root decay, optimizing soil moisture retention, and providing uniform light supply, while offering strong weed suppression and antibacterial functions, thereby increasing yield and resource efficiency.
Smart Images

Figure 112026023621006-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a microporous hybrid mulching material comprising graphene oxide and a method for manufacturing the same. Background Technology
[0002] Agricultural mulching materials are an essential agricultural technology for soil management and improving crop productivity, and their importance is increasing.
[0003] Although polymer films and the like were used as conventional mulching materials, they had negative effects on crop growth, such as reduced aeration and black dust contamination, as soil temperatures rose during the summer. Insufficient aeration hindered soil respiration, inhibiting root respiration and causing waterlogging and disease outbreaks.
[0004] In addition, although mulching materials made of aluminum reflective film have pest repellent and fruit coloring enhancement effects, they lack durability, require complex manufacturing processes, and have problems with uneven light supply due to excessive specular reflection.
[0005] In addition, there were problems caused by the frequent replacement of mulching materials and the generation of waste due to a lack of durability and weather resistance. The problem to be solved
[0006] One objective of the present invention is to provide a new concept of microporous hybrid mulching material and a method for manufacturing the same, which not only offers excellent breathability and durability—a trade-off that could not be achieved with conventional mulching materials—but also has excellent weed growth inhibition, soil temperature regulation, and aids crop growth through optimized light reflection.
[0007] Specifically, we aim to provide a microporous hybrid mulching material and a method for manufacturing the same, which can improve the crop growth environment by improving the plant's growth environment through excellent breathability, facilitating air circulation to promote plant root respiration, and reducing root decay to increase yield.
[0008] In addition, we aim to provide a microporous hybrid mulching material that can improve farm income by optimizing crop growth through light reflection, and a method for manufacturing the same.
[0009] In addition, we aim to provide a microporous hybrid mulching material and a method for manufacturing the same, which offers a strong weed growth inhibition effect, uniforms soil thermal conductivity, retains soil moisture for longer periods to increase drought resistance, reduces irrigation frequency, and provides excellent soil temperature control, moisture / nutrient management, and photosynthetic efficiency.
[0010] Furthermore, we aim to provide a microporous hybrid mulching material and a method for manufacturing the same that can help the healthy growth of crops by additionally imparting antibacterial, antifungal, deodorizing, and soil purification functions, and overcome the limitations of existing mulching materials by integrally optimizing various functions such as disease suppression, thereby simultaneously enhancing agricultural productivity and resource efficiency. means of solving the problem
[0011] The inventors provide a next-generation mulching solution that dramatically improves agricultural productivity and maximizes resource utilization efficiency through an original design and functional synergy that overcomes the limitations of existing mulching materials. As a result of research conducted to achieve the above objective, the inventors developed a microporous hybrid mulching material having a laminated structure comprising a white microporous film of a specific composition and a black nonwoven fabric of a specific composition, and containing at least one perforated hole, thereby completing the present invention.
[0012] Specifically, the present invention was completed by discovering that the addition of graphene oxide improves thermal conductivity, thereby enhancing soil temperature control capabilities, and that a uniform and stable microporous structure can be formed through synergy with calcium carbonate, and that the combination of titanium dioxide (TiO2) and pearl masterbatch maximizes diffuse reflectance of light, enabling uniform light supply to the lower part of the crop. In addition, it was discovered that adding a compatibilizer prevents phase separation caused by an excessive amount of inorganic material and can modify the film surface to be hydrophilic.
[0013] One aspect of the present invention comprises a surface layer made of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer;
[0014] A bottom layer made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and a black pigment; and
[0015] An adhesive layer for bonding the above surface layer and bottom layer;
[0016] A microporous hybrid mulching material is provided, comprising a plurality of perforated holes passing through the surface layer, adhesive layer, and bottom layer.
[0017] In one embodiment, the perforated hole and the bottom layer may be impregnated with a hydrophilic surfactant.
[0018] In one embodiment, the perforated hole may be formed by thermal needle perforation or laser perforation while the surface layer, adhesive layer, and bottom layer are laminated.
[0019] In one embodiment, the hole diameter R1 of the perforated hole may be 0.1 to 0.5 mm and the spacing L1 may be 1 to 5 mm, but is not limited thereto.
[0020] In one embodiment, the white microporous film may have a double embossing structure with different diameters. In this way, by having a double embossing structure, the diffuse reflectance of light can be maximized in combination with the white pigment and pearl pigment, thereby enabling uniform light supply to the lower part of the crop.
[0021] In one embodiment, the white microporous film may comprise 3 to 10 weight% of low-density polyethylene (LDPE), 30 to 50 weight% of metallocene linear low-density polyethylene (mLLDPE), 40 to 60 weight% of calcium carbonate, 0.05 to 0.2 weight% of graphene oxide, 0.5 to 5 weight% of white pigment, 0.5 to 5 weight% of pearl pigment, and 1 to 5 weight% of a compatibilizer, but is not limited thereto.
[0022] In one embodiment, the white microporous film may have a thickness of 0.01 to 0.05 mm and a porosity of 10 to 50%, but is not limited thereto.
[0023] In one embodiment, the black nonwoven fabric may comprise 85 to 95 weight% of a base resin, 0.05 to 0.2 weight% of graphene oxide, 0.1 to 10 weight% of illite, and 0.5 to 5 weight% of a black pigment, but is not limited thereto.
[0024] In one embodiment, the black pigment may be carbon black.
[0025] In one embodiment, the black nonwoven fabric may have a basis weight of 15 to 80 g / m², but is not limited thereto.
[0026] In one embodiment, the black nonwoven fabric may be selected from polyester-based nonwoven fabrics, polyolefin-based nonwoven fabrics, and bicomponent nonwoven fabrics thereof, but is not limited thereto.
[0027] In one embodiment, the total thickness of the microporous hybrid mulching material may be 0.02 to 0.1 mm, but is not limited thereto.
[0028] In one embodiment, the microporous hybrid mulching material has a water vapor permeability of 500 g / m² according to ASTM F1249 or ASTM E96. 2 / 24h or greater, and air permeability measured according to ASTM D726 or DIN EN ISO 9237 (1995-12) is 100 L / m 2 It may be more than ·s, but is not limited thereto.
[0029] In one embodiment, the microporous hybrid mulching material may have a tensile strength of 20 N / 5 cm or more according to ASTM D5035, a tear strength of 5 N or more according to ASTM D1922, and a temperature change of ±2 to 3 ℃ according to ISO 9869, but is not limited thereto.
[0030] In one embodiment, the microporous hybrid mulching material may have a specular reflectance of 5% or less according to ASTM E1396 and a haze of 80% or more according to ASTM D1003, but is not limited thereto.
[0031] Another aspect of the present invention comprises a first step of laminating a surface layer made of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer; and a bottom layer made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and a black pigment through an adhesive layer;
[0032] A second step of forming a plurality of perforated holes by thermal needle perforation or laser perforation while the above surface layer, adhesive layer, and bottom layer are laminated;
[0033] A method for manufacturing a microporous hybrid mulching material comprising
[0034] In one embodiment, the adhesive layer may be laminated by extrusion coating of a white microporous film and a black nonwoven fabric, or laminated by a dry lamination method using a heat bonding, ultrasonic bonding, or an adhesive selected from hot melt adhesives and water-based polyurethane adhesives.
[0035] In one embodiment, the hole diameter R1 of the perforated hole may be 0.1 to 0.5 mm, and the spacing L1 may be 1 to 5 mm.
[0036] In one embodiment, the method may further include the step of impregnating the microporous hybrid mulching material having the perforated holes formed therein with a hydrophilic surfactant, or spray-applying a hydrophilic surfactant so that the hydrophilic surfactant is impregnated into the perforated holes and the bottom layer.
[0037] In one embodiment, the method may further include the step of performing a hydrophilic treatment selected from corona treatment or plasma treatment on the surface layer of the microporous hybrid mulching material having the perforated holes formed therein before impregnating or applying the hydrophilic surfactant.
[0038] In one embodiment, the white microporous film is,
[0039] a) a step of manufacturing a sheet by melt-extruding a composition comprising 3 to 10 wt% low-density polyethylene (LDPE), 30 to 50 wt% metallocene linear low-density polyethylene (mLLDPE), 40 to 60 wt% calcium carbonate, 0.05 to 0.2 wt% graphene oxide, 0.5 to 5 wt% white pigment, 0.5 to 5 wt% pearl pigment, and 1 to 5 wt% compatibilizer;
[0040] b) a step of manufacturing a microporous film by biaxially stretching the above sheet;
[0041] c) a step of forming a double embossing structure with different diameters on the surface of the microporous film;
[0042] It may be manufactured including.
[0043] In one embodiment, the black nonwoven fabric may comprise the step of manufacturing the nonwoven fabric using a composition comprising 85 to 95 weight% of a base resin, 0.05 to 0.2 weight% of graphene oxide, 0.1 to 10 weight% of illite, and 0.5 to 5 weight% of a black pigment. Effects of the invention
[0044] A mulching material according to one embodiment of the present invention has excellent breathability and facilitates air circulation to promote respiration of crop roots, which can increase yields by reducing root decay, and can help crop growth by maintaining soil quality, temperature, and humidity appropriately through normal soil respiration.
[0045] In addition, light reflection of a white microporous film can be optimized by combining graphene oxide, calcium carbonate, white pigment, pearl pigment, and a compatibilizer, and uniform light supply to the lower part of the crop can be enabled by maximizing the diffuse reflectance of light. Furthermore, if double embossing is formed, the diffuse reflectance of light can be further maximized, improving the crop growth environment, thereby increasing yield and sugar content.
[0046] In addition, illite is added along with graphene oxide to the lower black spunbond nonwoven fabric layer to provide a strong weed suppression effect, and graphene oxide and illite can help promote healthy crop growth by uniformizing the thermal conductivity of the soil and additionally imparting antibacterial, antifungal, deodorizing, and soil purification functions.
[0047] In addition, the Hybrix mulching material according to one embodiment of the present invention has ultra-precision pinholes with a diameter of about 0.1 mm to 0.5 mm formed through a perforation method such as thermal piercing, and by impregnating a hydrophilic surfactant through these pinholes, the hydrophilic functional groups of graphene oxide can retain soil moisture for a longer period, thereby increasing drought resistance and reducing the frequency of irrigation.
[0048] In addition, by simultaneously including graphene oxide and illite in the bottom layer, additional antibacterial, antifungal, deodorizing, and soil purification functions can be provided to support the healthy growth of crops.
[0049] A mulching material according to one embodiment of the present invention can be applied to the growth of crops such as fruit trees and vegetables. Brief explanation of the drawing
[0050] FIG. 1 is a cross-sectional view showing the laminated structure of a microporous hybrid mulching material according to one embodiment of the present invention. FIG. 2 is a photograph illustrating a double embossing structure formed on the surface of a white microporous film according to one embodiment of the present invention. FIG. 3 is a photograph illustrating a perforated hole of a microporous hybrid mulching material according to one embodiment of the present invention. Specific details for implementing the invention
[0051] The present invention will be described in more detail below. However, the following specific examples or embodiments are merely references for the detailed explanation of the present invention and are not limited thereto, and the present invention may be implemented in various forms.
[0052] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. The terms used in the description of the present invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.
[0053] Additionally, the singular form used in the specification and the appended claims may be intended to include the plural form unless specifically indicated otherwise in the context.
[0054] Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0055] Furthermore, unless otherwise specifically defined in the present invention, when a layer or member is described as being located “on” another layer or member, this includes not only cases where a layer or member is in contact with another layer or member, but also cases where another layer or member exists between two layers or members.
[0056] Additionally, terms used herein such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the said sense, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosed content in which precise or absolute values are mentioned to aid in understanding the invention.
[0057] In the present invention, 'HYBRIX' refers to a mulching material in which a porous film and a non-woven fabric are laminated, and which can improve the quality of crops, particularly their sugar content (Brix).
[0059] One embodiment of the microporous hybrid mulching material of the present invention, as shown in FIG. 1, comprises a surface layer (100) made of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer;
[0060] A bottom layer (200) made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and a black pigment; and
[0061] An adhesive layer (300) for bonding the above surface layer and bottom layer;
[0062] It includes a plurality of holes (400) passing through the surface layer, adhesive layer, and bottom layer.
[0063] By including perforated holes (400) in this manner, root respiration can be facilitated through air circulation, and root decay can be reduced to increase yield. By allowing the soil to respire normally and maintaining soil quality, temperature, and humidity appropriately, crop growth can be aided. In other words, by allowing well-compacted soil to breathe, root health is enhanced, and crop growth can be optimized through light reflection. The perforated holes may be formed with multiple perforated holes at regular intervals.
[0064] The above-mentioned perforated holes may be formed by thermal needle perforation or laser perforation while the surface layer, adhesive layer, and bottom layer are laminated. In particular, thermal needle perforation forms a molten reinforcing ring around the pinhole, which can significantly increase the durability of the pinhole itself and prevent tearing. For example, the hole diameter R1 of the above-mentioned perforated holes may be 0.1 to 0.5 mm and the spacing L1 may be 1 to 5 mm; however, it is not limited thereto, but within the above range, the supply of moisture and nutrients can be smoothly carried out. Furthermore, it can suppress the evaporation of soil moisture, retain moisture, and enable the supply of moisture and nutrients necessary for crops, thereby reducing drought damage and increasing the efficiency of fertilizer utilization. Additionally, it can promote smooth air and gas exchange between the soil and the atmosphere, assisting root respiration and maintaining a healthy soil ecosystem.
[0065] In one embodiment of the microporous hybrid mulching material of the present invention, the perforated holes (400) and the bottom layer (200) may be impregnated with a hydrophilic surfactant and may serve to preserve soil moisture and improve drought resistance. The hydrophilic surfactant may be impregnated by immersion or spray application. By impregnating with a hydrophilic surfactant in this manner, moisture penetration through the perforated holes is promoted, water droplet formation is prevented, and the adhesion of foreign substances such as dust is prevented, thereby increasing light transmittance and reducing the risk of pathogen outbreaks.
[0066] In one embodiment of the microporous hybrid mulching material of the present invention, as illustrated in FIG. 2, the white microporous film may have a double embossing structure with different diameters. For example, it may include a first embossing portion with a diameter in the nanometer range and a second embossing portion with a diameter in the micrometer range. By having a double embossing structure that simultaneously includes micrometer and nanometer units, it is possible to provide optimal diffuse reflection and anti-blocking effects. In addition, it can provide a low specular reflection of 5% or less and provide uniform light diffusion, and due to the optimization of light reflection, it can provide effects that aid crop growth, increase yield, and further increase the sugar content of the fruit.
[0067] The total thickness of the microporous hybrid mulching material according to one embodiment of the present invention may be 0.02 to 0.1 mm, but is not limited thereto. Within this range, it may be advantageous for storage and construction due to its thin thickness, while also having excellent durability and mechanical properties.
[0068] A microporous hybrid mulching material according to one embodiment of the present invention can provide excellent breathability despite its thin thickness, while simultaneously offering excellent durability and weather resistance. In addition, it can provide various functions such as improved soil temperature regulation, enhanced soil moisture retention, increased photosynthetic efficiency, and disease suppression.
[0069] In one embodiment, the microporous hybrid mulching material has a water vapor permeability of 500 g / m² according to ASTM F1249 or ASTM E96. 2 / 24h or more, 500 to 10,000 g / m² 2 / 24h, 1,000 to 10,000 g / m² 2 / 24h, 2,000 to 10,000 g / m² 2 / 24h, 3,000 to 10,000 g / m² 2 / 24h, 4,000 to 10,000 g / m² 2 / 24h, 5,000 to 10,000 g / m² 2 It may be / 24h, but is not limited to this.
[0070] In addition, air permeability measured according to ASTM D726 or DIN EN ISO 9237 (1995-12) is 100 L / m 2 ·s or more, 100 to 300 L / m 2 It may be ·s, but is not limited to this.
[0071] In addition, the tensile strength according to ASTM D5035 may be 20 N / 5cm or more, 20 to 100 N / 5cm, 20 to 90 N / 5cm, or 20 to 80 N / 5cm, but is not limited thereto. The above tensile strength is expressed in Newtons (N) as the maximum tensile force (force) that a material sample with a width of 5cm can withstand.
[0072] In addition, the tear strength according to ASTM D1922 may be 5 N or more, 5 to 20 N, 5 to 18 N, or 5 to 15 N, but is not limited thereto.
[0073] In addition, the change in soil temperature according to ISO 9869 may be ±2 to 3 ℃, which confirms that the ability to control soil temperature is excellent compared to mulching materials consisting only of conventional films or non-woven fabrics, which have a change of ±4 ℃ or more. As the hybrid mulching material according to one embodiment of the present invention includes graphene oxide, the thermal conductivity is improved, the change in soil temperature can be minimized, and the soil temperature can be maintained uniformly.
[0074] In addition, the microporous hybrid mulching material may have a specular reflectance of 5% or less, 4% or less, 3% or less, or 1% or more according to ASTM E1396, and may be any value between these values. In addition, the haze may have a value of 80% or more, 85% or more, 95% or less, or 90% or less according to ASTM D1003, and may be any value between these values.
[0075] In addition, the weed suppression rate may be 95% or higher, 96% or higher, 97% or higher, 98% or higher, or 100% or lower, and may be any value between the above figures. In addition, the yield may be increased compared to using conventional black or white film or non-woven fabric mulching material alone.
[0076] In addition, the dust adhesion rate may be less than 5%, 4% or less, 3% or less, 2% or less, 1% or less, or 0% or more, and may be any value between the above values. That is, by including a hydrophilic treatment of the surface and a surfactant impregnation process, the adhesion of foreign substances such as dust can be prevented, and the white surface layer can be maintained to provide the effect of maintaining light reflection. In addition, the sugar content of the fruit can be increased by 1.5 times or more, 1.5 times or 3 times, and the crop yield can be increased by 15% or more, or 15 to 20%.
[0078] The following describes each component of the present invention in more detail.
[0079] Surface layer
[0080] In one embodiment of the present invention, the surface layer is located on top of the mulching material and serves to regulate the light environment and soil temperature of the crop. Specifically, the surface layer is composed of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer.
[0081] The white microporous film may have a double embossing structure formed on its surface having different diameters. The double embossing structure may consist of a first embossing structure with a diameter in the nanometer range and a second embossing structure with a diameter in the micrometer range, formed simultaneously on the film surface. The embossing structure may be formed by passing the white microporous film through an embossing roller having an embossing formed thereon, but is not limited thereto.
[0082] As such, by having a dual embossing structure that simultaneously includes micrometer and nanometer-sized embossing structures, it is possible to provide optimal diffuse reflection and anti-blocking effects. In addition, it can provide a low specular reflection of 5% or less and uniform light diffusion, and due to the optimization of light reflection, it can provide effects that aid crop growth, increase yield, and further increase the sugar content of fruits.
[0083] For example, the first embossing structure may have a diameter of 10 to 50 nm, and the second embossing structure may have a diameter of 30 to 200 μm, but is not limited thereto. Additionally, the depth of the embossing may be 50 to 200 μm, and within this range, optimal diffuse reflection and anti-blocking effects can be provided.
[0084] The first embossing structure and the second embossing structure may be one or more structures selected from dot shapes, grid shapes, etc., but are not limited thereto. The double embossing may not include an embossing structure, or may increase the diffuse reflectance by more than 20% compared to a diamond embossing with a grid structure. In addition, the addition of graphene oxide, combined with the double embossing structure, can optimize not only light management but also geothermal management. Furthermore, it can prevent blocking of the film, thereby improving handling and work convenience.
[0085] Additionally, if necessary, the white microporous film may have its surface hydrophilically treated by performing a hydrophilic treatment selected from corona treatment or plasma treatment. By treating the surface hydrophilically in this way, the impregnation or application of a hydrophilic surfactant can be facilitated more smoothly, and the hydrophilic surface prevents foreign substances such as dust from adhering to the surface, thereby continuously maintaining light reflection efficiency.
[0086] The white microporous film may comprise 3 to 10 weight% of low-density polyethylene (LDPE), 30 to 50 weight% of metallocene linear low-density polyethylene (mLLDPE), 40 to 60 weight% of calcium carbonate, 0.05 to 0.2 weight% of graphene oxide, 0.5 to 5 weight% of white pigment, 0.5 to 5 weight% of pearl pigment, and 1 to 5 weight% of a compatibilizer.
[0087] The above low-density polyethylene (LDPE) may be used to ensure the stability of the bubbles by maintaining the melt strength of the bubbles at a constant level, and may be used in an amount of 3 to 10 weight percent.
[0088] The above metallocene linear low-density polyethylene (mLLDPE) may be used to improve the tensile strength and tear strength of the film, and to prevent pinholes in low basis weight films, as well as to improve moisture permeability and air permeability, and may be used in an amount of 30 to 50 weight%. In addition, it may be used with a density of 0.920 to 0.945 g / cm³, and considering elongation, it may be used with a melt index (MI) of 2.0 to 4.5 g / 10 min measured at 190 ℃ and 2.16 kg according to ASTM D1238.
[0089] The calcium carbonate mentioned above is essential for realizing micropority in the film, going beyond simply being an inorganic filler, and can perform the function of controlling geothermal heat, providing breathability, and controlling moisture through combination with graphene oxide. The average particle size of the calcium carbonate may be 0.1 to 10 μm, but is not limited thereto. Additionally, the calcium carbonate may be surface-coated with a fatty acid such as stearic acid, and the coating amount may be 0.5 to 5 weight%. By using calcium carbonate surface-coated with a fatty acid in this way, the miscibility with the low-density polyethylene and metallocene linear low-density polyethylene can be improved.
[0090] The content of the calcium carbonate may be 40 to 60 weight percent, and within this content range, the amount of plastic used can be drastically reduced, thereby providing a carbon dioxide reduction and eco-friendly material, and enhancing the sustainability of the mulching material.
[0091] The graphene oxide mentioned above can improve the thermal conductivity of the film, thereby ensuring a uniform soil temperature distribution and effectively alleviating high-temperature stress. Furthermore, by increasing the cation exchange capacity (CEC), the graphene oxide can aid in the crop's absorption of fertilizer components or minerals. In particular, it can increase nutrient absorption efficiency by being linked to the increase in sugar content (increased photosynthetic efficiency), which is emphasized in hybrid farming methods. For example, graphene oxide promotes the absorption of photosynthetic-related minerals (e.g., Mg, Fe) from the soil and helps improve sugar content, thereby indirectly promoting photosynthetic efficiency aimed at increasing Brix, which is a key focus in hybrid agriculture.
[0092] The graphene oxide may have an average particle size of 1 to 10 nm, and while the above size provides excellent dispersibility, it is not limited thereto.
[0093] The content of the graphene oxide may be 0.05 to 0.2 weight%, but is not limited thereto.
[0094] Commercialized examples of the above graphene oxide include HGO6D100 from Grapheneol Co., Ltd., but are not limited thereto.
[0095] The above white pigment is used to provide a white microporous film to efficiently perform light reflection, and for example, titanium dioxide (TiO2) may be used. The above white pigment provides strong whiteness and UV reflectivity, thereby suppressing excessive rise in soil temperature and increasing the opacity of the film, which can indirectly contribute to weed suppression. The content of the above white pigment may be 0.5 to 5 weight%, 7 to 4 weight%, or 7 to 3 weight%, but is not limited thereto. The above white pigment may be titanium dioxide with an average particle size of 5 to 20 μm, but is not limited thereto.
[0096] The above white pigment may be manufactured as a masterbatch, and commercially available examples include titanium dioxide from Hanil Toyo Co., Ltd.
[0097] By using the above pearl pigment mixed with the above white pigment, it is possible to efficiently reflect light and impart a unique effect of interfering with and scattering light. Through this, the problem of excessive specular reflection (hot spots) in conventional aluminum films can be resolved, and light can be uniformly diffused to the lower leaves of crops, thereby dramatically increasing photosynthetic efficiency. In addition, it can induce even coloring of fruits and reduce light stress. The content of the above pearl pigment may be 0.5 to 5 weight%, 7 to 4 weight%, or 7 to 3 weight%, but is not limited thereto.
[0098] The above pearl pigment may be a mica coated with a metal oxide on its surface and may have an average particle size of 5 to 20 μm. In addition, a masterbatch may be used, and commercially available examples include Hanil Toyo's Pearl Masterbatch.
[0099] The above compatibilizer can be used to improve the miscibility between the calcium carbonate and low-density polyethylene and metallocene linear low-density polyethylene, and to improve the miscibility of graphene oxide. That is, the calcium carbonate content can be used up to 40 to 60 weight%, and problems such as phase separation, resulting powder generation, pinholes, gels, and die build-up can be resolved. In addition, it can also contribute to modifying the surface of the hydrophobic hybrid mulching material to be hydrophilic. The content of the above compatibilizer may be 1 to 5 weight%, but is not limited thereto.
[0100] The type of the above compatibilizer is not limited as long as it is commonly used in the relevant field; for example, maleic anhydride-grafted polyolefins may be used. An example of a commercially available compatibilizer is SKFP’s OREVAC. ® You can use 18341, etc.
[0101] In addition, the white microporous film may further include one or more additives selected from the group consisting of antioxidants, UV stabilizers, lubricants, etc., as needed.
[0102] Examples of the above antioxidants may include one or more selected from phenolic antioxidants and phosphorus-based antioxidants, and may be used without limitation as long as they are commonly used in the relevant field. For example, a mixture of 0.1 to 0.5 weight% of a primary phenolic antioxidant and 0.1 to 0.5 weight% of a secondary phosphorus-based antioxidant may be used. A commercially available example is BASF’s Irganox. ® 3114 (I-phenolic), Irgafos ® 168 (6260)(2nd handover) etc. can be used.
[0103] The above UV stabilizer may be used without limitation as long as it is commonly used in the relevant field. Commercially available examples include BASF’s Chimasorb 119 and Tinuvin 622, and a mixture thereof may be used. For example, 0.1 to 1.0 weight% of Chimasorb 119 and 0.1 to 1.0 weight% of Tinuvin 622 may be mixed and used.
[0104] The above lubricant may be used without limitation as long as it is commonly used in the relevant field. For example, one or more selected from zinc stearate (ZnSt) and calcium stearate (CaSt) may be used. For example, 0.1 to 0.5 weight% of zinc stearate (ZnSt) and 0.1 to 0.5 weight% of calcium stearate (CaSt) may be mixed and used.
[0105] For example, the white microporous film may comprise 3 to 10 weight% of low-density polyethylene (LDPE), 30 to 50 weight% of metallocene linear low-density polyethylene (mLLDPE), 40 to 60 weight% of calcium carbonate, 0.05 to 0.2 weight% of graphene oxide, 0.5 to 5 weight% of white pigment, 0.5 to 5 weight% of pearl pigment, 1 to 5 weight% of compatibilizer, 0.1 to 2 weight% of UV stabilizer, 0.1 to 1 weight% of antioxidant, and 0.1 to 1 weight% of lubricant.
[0106] The above white microporous film may have a thickness of 0.01 to 0.05 mm and a porosity of 10 to 50%, but is not limited thereto. As described above, by having a microporous structure, soil aeration and gas exchange can be facilitated, thereby solving the problems of soil waterlogging and inhibition of root respiration and promoting healthy root development.
[0107] Floor layer
[0108] The aforementioned bottom layer is located at the bottom of the mulching material and can provide powerful weed suppression and thermal insulation functions. Due to its black color, it completely blocks sunlight, effectively inhibiting weed germination and growth beneath the mulching material; this significantly reduces herbicide use and contributes to labor savings. Furthermore, it acts as a physical support layer for the white microporous film of the surface layer, maximizing the durability and tear resistance of the entire mulching material. Additionally, due to its black nature, it absorbs geothermal heat to maintain stable soil temperatures even during cold periods, thereby promoting early crop growth.
[0109] The above-mentioned bottom layer consists of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and black pigment. For example, it may be a black spunbond nonwoven fabric and can provide excellent strength, elongation, UV resistance, and breathability. By using a combination of graphene oxide, illite, and black pigment in this way, the overall heat management function can be enhanced through synergy with the graphene oxide-added surface layer. Furthermore, the inclusion of illite can improve the soil environment beneath the mulching material and further promote crop growth. Illite can provide the effect of purifying the soil by adsorbing and removing harmful gases such as benzene, toluene, formaldehyde, and ammonia, as well as adsorbing heavy metals. Additionally, it can reduce the risk of disease outbreaks through antibacterial action against harmful pathogens such as Pseudomonas aeruginosa, E. coli, and Staphylococcus aureus, and fungal neutralization functions, while enhancing crop vitality through far-infrared and negative ion emission functions.
[0110] Furthermore, the graphene oxide possesses antimicrobial properties that can inhibit the growth of pathogenic microorganisms, such as fungi and bacteria, in the soil surrounding crops. This can lower the incidence of crop diseases and promote healthy growth, thereby allowing for the expectation of pathogen suppression and improved soil hygiene. In this way, the synergy between illite and graphene oxide normalizes soil respiration, which can enhance root health. Additionally, the hydrophilic functional groups (epoxide, hydroxyl, etc.) of graphene oxide adsorb moisture, helping the mulching material retain soil moisture for a longer period. This can increase drought resistance and provide the potential to reduce the frequency of irrigation.
[0111] The black nonwoven fabric may comprise 85 to 95 weight% of base resin, 0.05 to 0.2 weight% of graphene oxide, 0.1 to 10 weight% of illite, and 0.5 to 5 weight% of black pigment, and is not limited thereto, but may be advantageous for achieving the desired effect within the above content range.
[0112] The graphene oxide above is the same as previously described.
[0113] The illite may have an average particle size of 1 to 15 μm, but is not limited thereto. The addition of the illite can complement the physical and chemical performance of the nonwoven fabric and contribute to soil environmental purification and crop growth promotion.
[0114] The black pigment may be carbon black, but is not limited thereto. The content of the black pigment may be 0.5 to 5 weight% or 1 to 4 weight%, and within this range, light blocking can be ensured to suppress photosynthesis of weeds.
[0115] The black nonwoven fabric may have a basis weight of 15 to 80 g / m², and, although not limited thereto, may be provided with durability and mechanical strength within the above range. The basis weight may be flexibly adjusted according to the cultivated crop and the required durability.
[0116] The above black nonwoven fabric may be selected from polyester-based nonwoven fabrics, polyolefin-based nonwoven fabrics, and bicomponent nonwoven fabrics thereof, and may be a spunbond nonwoven fabric manufactured according to a manufacturing method typically used in the field.
[0117] <Adhesive layer>
[0118] The adhesive layer is configured to bond the surface layer and the bottom layer. The adhesive layer may be formed by laminating a black nonwoven fabric and then heat-pressing it during the process of manufacturing a white microporous film, or by heat-pressing and laminating the separately manufactured white microporous film and black nonwoven fabric. Alternatively, it may be formed by ultrasonic bonding, or by a dry lamination method using an adhesive selected from hot melt adhesives and water-based polyurethane adhesives, but is not limited thereto.
[0119] Method for manufacturing microporous hybrid mulching material
[0120] A method for manufacturing a microporous hybrid mulching material according to one aspect of the present invention is,
[0121] A first step of laminating a surface layer made of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, white pigment, pearl pigment, and a compatibilizer; and a bottom layer made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and black pigment through an adhesive layer;
[0122] A second step of forming a plurality of perforated holes by thermal needle perforation or laser perforation while the above surface layer, adhesive layer, and bottom layer are laminated;
[0123] Includes
[0124] Another mode is,
[0125] A step of manufacturing a surface layer composed of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer;
[0126] A step of manufacturing a bottom layer made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and a black pigment;
[0127] A step of forming an adhesive layer by bonding the above surface layer and bottom layer; and
[0128] A step of forming a perforated hole by thermal needle perforation or laser perforation while the surface layer, adhesive layer, and bottom layer are laminated;
[0129] Includes
[0130] Since each of the above components is the same as previously explained, a redundant explanation is omitted.
[0131] In one embodiment, the perforated holes may be formed at regular intervals, for example, the hole diameter R1 may be 0.1 to 0.5 mm and the interval L1 may be 1 to 5 mm, but is not limited thereto. The shape of the perforated holes may be circular, triangular, or square, etc., but is not limited thereto.
[0132] In one embodiment, the method may further include the step of impregnating the microporous hybrid mulching material having the perforated holes with a hydrophilic surfactant, or spray-applying the hydrophilic surfactant, so that the hydrophilic surfactant is impregnated into the perforated holes and the bottom layer. For example, the hydrophilic surfactant may be impregnated into the interior of the mulching material and the bottom layer through the perforated holes.
[0133] Additionally, the method may include a drying step after impregnating with the hydrophilic surfactant. Through the drying process, the surfactant is fixed to the surface of the mulching material, allowing it to stably exert its effect for a long period. The drying temperature may be 80°C to 120°C, but is not limited thereto.
[0134] The above hydrophilic surfactant is not limited and non-ionic or anionic surfactants, etc., may be used. It may be selected considering permanent affinity for the polyethylene surface and environmental safety. For example, polyoxyethylene alkyl ethers, sorbitan fatty acid esters, etc., may be used. The above hydrophilic surfactant may be applied and impregnated in the form of an aqueous solution mixed with water at a content of 0.1 to 1 weight%. Within the above content range, wettability is improved and persistence may be provided. Commercially available examples of hydrophilic surfactants include AB100 of Jungil Yuhwa, but are not limited thereto.
[0135] In one embodiment, the method may further include the step of performing a hydrophilic treatment selected from corona treatment or plasma treatment on the surface layer of the microporous hybrid mulching material having the perforated holes formed therein before impregnating or applying the hydrophilic surfactant. This process can serve to significantly increase the efficiency and sustainability of the subsequent hydrophilic surfactant treatment by forming active radicals and polar groups on the film surface. The energy of the corona treatment or plasma treatment may be 30 dynes / cm to 50 dynes / cm, but is not limited thereto.
[0136] In one embodiment, the adhesive layer is configured to bond the surface layer and the bottom layer. The adhesive layer may be formed by laminating a black nonwoven fabric and then heat-pressing it during the process of manufacturing a white microporous film, or by laminating the white microporous film and the black nonwoven fabric, respectively, by heat-pressing them. Alternatively, it may be formed by ultrasonic bonding, or by a dry lamination method using an adhesive selected from hot melt adhesives and water-based polyurethane adhesives, but is not limited thereto. When applying the adhesive, the application amount may be 5 g / m² to 20 g / m², but is not limited thereto.
[0137] For example, the adhesive layer may be formed by applying a water-based polyurethane adhesive, and the adhesive may be applied using a copper plate of a gravure coater. The copper plate of the gravure coater may be a gravure coater copper plate with a surface laser-engraved with a grid pattern of 10 to 300 mesh. By applying the adhesive using the copper plate, breathability can be maintained and moisture permeability can be further improved.
[0138] In one embodiment, the method for manufacturing the white microporous film is
[0139] a) a step of manufacturing a sheet by melt-extruding a composition comprising 3 to 10 wt% low-density polyethylene (LDPE), 30 to 50 wt% metallocene linear low-density polyethylene (mLLDPE), 40 to 60 wt% calcium carbonate, 0.05 to 0.2 wt% graphene oxide, 0.5 to 5 wt% white pigment, 0.5 to 5 wt% pearl pigment, and 1 to 5 wt% compatibilizer;
[0140] b) a step of manufacturing a microporous film by biaxially stretching the above sheet;
[0141] c) a step of forming a double embossing structure with different diameters on the surface of the microporous film;
[0142] It may include.
[0143] In step a) above, the composition may be manufactured into pellets by precise preparation in a compounding device, dried at 80 to 90°C for 1 to 2 hours, and then controlled to have a moisture content of 500 ppm or less.
[0144] The process of manufacturing the sheet by melt extrusion described above may involve using a blown extruder and melt extrusion at 130 to 160°C.
[0145] In step b) above, the microporous film may be manufactured by stretching the material 2.0 to 4.0 times in the CD (Cross-Direction) direction using a BUR (Blow Up Ratio) during extrusion, followed by extrusion molding, and then stretching it 3.0 to 6.0 times in the MD (Machine Direction) direction, but is not limited thereto.
[0146] The aforementioned two-step anisotropic stretching process efficiently forms uniform and fine voids around calcium carbonate particles, optimizing the mechanical strength and microporous properties of the film. Additionally, the addition of graphene oxide disperses during the stretching process, which can uniformly improve thermal conductivity.
[0147] Step c) above may involve forming a double embossing on the surface of the film using a separate embossing roller before or after the film is cooled. The double embossing structure may be formed by simultaneously forming a first embossing structure with a diameter in the nanometer range and a second embossing structure with a diameter in the micrometer range on the surface of the film. The embossing structure may be formed by passing the white microporous film through an embossing roller in which the embossing is formed, but is not limited thereto. When passing through the embossing roller, the roller temperature may be 80 to 150°C and the pressure of the embossing roller may be 50 to 150 kg / cm², but is not limited thereto.
[0148] As such, by having a dual embossing structure that simultaneously includes micrometer and nanometer-sized embossing structures, it is possible to provide optimal diffuse reflection and anti-blocking effects. In addition, it can provide a low specular reflection of 5% or less and uniform light diffusion, and due to the optimization of light reflection, it can provide effects that aid crop growth, increase yield, and further increase the sugar content of fruits.
[0149] For example, the first embossing structure may have a diameter of 10 to 50 nm, and the second embossing structure may have a diameter of 30 to 200 μm, but is not limited thereto. Additionally, the depth of the embossing may be 50 to 200 μm, and within this range, optimal diffuse reflection and anti-blocking effects can be provided.
[0150] The first embossing structure and the second embossing structure may be one or more structures selected from dot shapes, grid shapes, etc., but are not limited thereto. The double embossing may not include an embossing structure, or may increase the diffuse reflectance by more than 20% compared to a diamond embossing with a grid structure. In addition, the addition of graphene oxide, combined with the double embossing structure, can optimize not only light management but also geothermal management. Furthermore, it can prevent blocking of the film, thereby improving handling and work convenience.
[0151] In one embodiment, the method for manufacturing the black nonwoven fabric may include the step of manufacturing a nonwoven fabric using a composition comprising 85 to 95 weight% of a base resin, 0.05 to 0.2 weight% of graphene oxide, 0.1 to 10 weight% of illite, and 0.5 to 5 weight% of a black pigment. The base resin may be a polyolefin resin such as polypropylene or polyethylene, or a polyester resin such as polyethylene terephthalate. In addition, in one embodiment, the nonwoven fabric may be a spunbond nonwoven fabric manufactured from the base resins, or a bicomfort nonwoven fabric in which a nonwoven fabric manufactured using the polyolefin resin and the polyester resin is laminated. The graphene oxide, illite, and black pigment are the same as those previously described.
[0152] In one embodiment, the black spunbond nonwoven fabric layer may be composed of polypropylene spunbond, polyethylene terephthalate spunbond, or one of their bicomponents.
[0154] The present invention will be explained in more detail below based on the following examples and comparative examples. However, the following examples and comparative examples are merely illustrative of the present invention and are not intended to limit the present invention.
[0155] The following physical properties were evaluated as follows.
[0156] 1) Specular Reflectance
[0157] Specular reflectance evaluated the possibility of hot spots occurring where sunlight is concentrated in only a specific direction.
[0158] Measurements were taken according to ASTM E1396. An integrating sphere was mounted on a spectrophotometer to measure the ratio of light incident on the surface of the mulching material that is reflected head-on in the visible and near-infrared regions (400 nm–1000 nm).
[0159] 2) Diffuse Reflectance / Haze
[0160] Diffuse reflectance is an evaluation method that quantifies the efficiency of light spreading uniformly to the lower part of the crop. Haze was measured according to ASTM D1003, and a spectrophotometer was used to measure the ratio of light incident on the sample that is scattered and reflected in all directions. Haze is the ratio of scattered light to transmitted light.
[0161] 3) Water vapor transmission rate (WVTR)
[0162] The water vapor release capacity for preventing soil moisture and root respiration was evaluated.
[0163] It was evaluated according to ASTM F1249 or ASTM E96.
[0164] Cup Method: Under constant temperature and humidity conditions, the rate at which moisture inside the container covering the sample evaporated and passed through the sample (weight loss) was measured.
[0165] 4) Air Permeability
[0166] The 'breathing' capacity of the soil, that is, gas exchange efficiency such as O2 supply and CO2 emission, was evaluated. Air permeability was evaluated according to ASTM D726 or DIN EN ISO 9237 (1995-12), and the time required for a certain volume of air to pass through a sample of a certain area under a specified pressure was measured.
[0167] 5) Change in ground temperature (temperature stabilization)
[0168] Evaluation was conducted according to ISO 9869. Precision thermocouples or digital temperature sensors were installed in the soil beneath the mulch (depths of 5 cm and 10 cm), and changes in soil temperature during the day, night, and season were continuously monitored for a certain period.
[0169] 6) Weed incidence rate and biomass
[0170] Per unit area (m²) within the cultivation zone 2 The number of weeds and the dry weight of the weeds collected after a certain period were measured. The amount was evaluated as a relative quantity compared to the control group.
[0171] 7) Sugar content (Brix)
[0172] The juice of harvested crops (e.g., fruits) was extracted, and the sugar content was measured using a digital refractometer.
[0173] 8) Yield and Biomass
[0174] Total yield per unit area (kg / a) of crops at harvest time and growth indicators (plant height, number of leaves, weight, etc.) for each crop were measured and compared.
[0175] 9) Tensile Strength
[0176] Measurements were taken according to ASTM D5035. The sample was cut to a uniform width, clamped in a tensile testing machine, and the maximum load until fracture was measured.
[0177] 10) Tear Resistance
[0178] Measurements were taken according to ASTM D1922 (Elmendorf method). A small notch was made in the sample beforehand, and the force (load) required to tear it was measured.
[0180] [Example 1]
[0181] 1) Preparation of white microporous film
[0182] LDPE (Hanwha Solutions, LDPE 955, density: 0.913 g / cm³, melt index (7.7 g / 10 min at 190 ℃, 2.16 kg load) 7 wt%, mLLDPE (LG Chem, LUCENE HP3527CN, density: 0.927 g / cm³, melt index (3.5 g / 10 min at 190 ℃, 2.16 kg load) 38 wt%, calcium carbonate (Yabashi Limestone, YK-1C, average particle size 1.7 µm) 49 wt%, graphene oxide (Grapheneol, HGO6D100) 0.1 wt%, titanium dioxide (average particle size 10 µm) as white pigment 1.5 wt%, pearl pigment (Hanil Toyo, Pearl Masterbatch, pearl pigment content 50 wt%) 1.5 wt%, compatibilizer Maleic anhydride-grafted low-density polyethylene resin (SKFP, OREVAC) ® 18341) 1.5 wt%, UV stabilizer (mixture of BASF’s Chimasorb 119 and BASF’s Tinuvin 622 in a 1:1 weight ratio) 0.4 wt%, primary phenolic antioxidant (BASF, Irganox ® 3114) 0.2 wt%, secondary phosphorus-based antioxidant (BASF, Irgafos ® A film with a thickness of 0.02 mm and a porosity of 30% was produced from a compound composition mixed with 0.2 wt% zinc stearate (ZnSt, BASF), 0.3 wt% calcium stearate (CaSt, BASF).
[0183] After manufacturing the film, it was heat-pressed with an embossing roller to produce a film having a double embossing structure on its surface as shown in Fig. 2. The diameter of the first embossing was 40 nm and the depth was 120 μm, and the diameter of the second embossing was 150 μm and the depth was 150 μm.
[0184] 2) Manufacture of black nonwoven fabric
[0185] A spunbond nonwoven fabric with a basis weight of 50 g / m² was used, prepared from a composition comprising 90 wt% polypropylene resin, 0.1 wt% graphene oxide, 6.9 wt% illite, and 3 wt% black pigment.
[0186] 3) Manufacture of microporous hybrid mulching material
[0187] A water-based polyurethane adhesive (Samho Chemical, SPU-7835) was applied by transfer coating to one side of the above-manufactured film and nonwoven fabric using a coating roller with a 200-mesh gravure coater plate laser-engraved with a grid pattern, and then laminated using a dry lamination method to form an adhesive layer. Next, a plurality of perforated holes were formed at regular intervals with a hole diameter R1 of 0.3 mm and a spacing L1 of 3 mm in the laminated body in which the film, adhesive layer, and nonwoven fabric were laminated using a heat needle perforation method.
[0188] Next, the laminate with the perforated holes formed thereon was immersed in an aqueous solution containing 1% by weight of an anionic surfactant (Jungil Emulsion, AB-100), removed, and dried.
[0189] The physical properties of the manufactured microporous hybrid mulching material were measured and are shown in Table 1 below.
[0191] [Example 2]
[0192] In the above Example 1, a microporous hybrid mulching material was prepared in the same manner as in Example 1, except that when preparing a white microporous film, a double embossing structure was formed on the surface, and then a corona treatment was performed on the surface was additionally included.
[0193] The physical properties of the manufactured microporous hybrid mulching material were measured and are shown in Table 1 below.
[0195] [Example 3]
[0196] In the above Example 1, a microporous hybrid mulching material was prepared in the same manner as in Example 1, except that the step of immersing the laminate with the perforated holes formed therein in an aqueous solution containing 1% by weight of an anionic surfactant (Jungil Emulsion, AB-100), removing it, and drying it was omitted.
[0197] The physical properties of the manufactured microporous hybrid mulching material were measured and are shown in Table 1 below.
[0199] [Comparative Example 1]
[0200] A black film with a thickness of 0.025 mm, used as an agricultural mulching agent, was used.
[0201] The physical properties were measured and are shown in Table 1 below.
[0203] [Comparative Example 2]
[0204] A white film with a thickness of 0.025 mm, used as an agricultural mulching agent, was used.
[0205] The physical properties were measured and are shown in Table 1 below.
[0207] [Comparative Example 3]
[0208] An aluminum reflective film with a thickness of 0.05 mm, used as an agricultural mulching agent, was used.
[0209] The physical properties were measured and are shown in Table 1 below.
[0211] [Comparative Example 4]
[0212] A non-woven fabric mulch used as an agricultural mulch was used.
[0213] The physical properties were measured and are shown in Table 1 below.
[0215] [Comparative Example 5]
[0216] In the above Example 3, when manufacturing the white microporous film, graphene oxide and a compatibilizer were not used, and the calcium carbonate content was increased by that amount. In addition, the film was manufactured in the same manner as Example 3, except that the step of forming a double embossing structure on the surface by heat-pressing with an embossing roller after manufacturing was omitted.
[0217] In addition, the black nonwoven fabric was manufactured using the same method as in Example 3, except that graphene oxide and illite were not used and the content of polypropylene resin was increased by that amount.
[0218] A laminate was prepared by laminating the white microporous film and black nonwoven fabric prepared in this manner in the same way as in Example 3, but the step of immersing in an aqueous solution of an anionic surfactant and drying as in Example 3 was omitted. The physical properties of the prepared laminate were measured and are shown in Table 1 below.
[0220] [Comparative Example 6]
[0221] A laminate was manufactured in the same manner as Comparative Example 5 above, and no perforated holes were formed after manufacturing the laminate. The physical properties of the manufactured laminate were measured and are shown in Table 1 below.
[0223] Example 1 Example 2 Example 3 Comparative Example 1 Specular reflectance (%) 4.4 4.3 4.4 5 Diffuse reflection (%) 87.7 88 87.8 10 Water vapor permeability (g / m² / 24h) 5,000 6,000 2,000 5 Breathability (L / m²·s) 400 450 400 No ventilation Change in ground temperature (°C) ±3 ±2 ±3 ±8 Weed suppression rate (%) 95 97 95 90 Yield growth rate (%) 20 22 20 standard Sugar content (°brix) 2.5 increase 3 increase 2.5 increase standard Dust accumulation (%) Less than 5 Less than 3 7 30 Tensile strength (N / 5cm) 20 or more 20 or more 20 or more 12 Tear strength (N) 5 or more 5 or more 5 or more 3
[0225] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Specular reflectance (%) 5 12 30 10 8 8 Diffuse reflection (%) 10 70 60 60 60 60 Water vapor permeability (g / m²) 2 / 24h) 5 50 10 200 300 150 Breathability (L / m²·s) No ventilation No ventilation No ventilation 95 No ventilation No ventilation Change in ground temperature (°C) ±8 ±6 ±7 ±5 ±6 ±6 Weed suppression rate (%) 90 70 70 85 90 90 Yield growth rate (%) standard 10 8 10 10 8 Sugar content (°brix) standard 1 1.2 1.2 1.3 1.1 Dust adhesion (%) 30 15 15 15 15 15 Tensile strength (N / 5cm) 12 15 10 15 16 16 Tear strength (N) 3 4 2 4 4 3
[0226] As shown in Table 1 above, Examples 1 and 2 according to the present invention exhibit uniform light diffusion with low specular reflection, and increased photosynthetic efficiency by supplying light to the lower leaves of the crop due to high diffuse reflectance. In addition, it was confirmed that the water vapor transmission rate improved by 100 to 1,000 times due to the inclusion of perforated holes. Furthermore, it was confirmed that the excellent breathability promotes root respiration and prevents excessive moisture. Additionally, it was confirmed that the inclusion of graphene oxide improved thermal conductivity, reduced soil temperature fluctuations to 30% or less, and maintained the soil temperature within ± 2 to 3 ℃. Moreover, it was confirmed that the weed suppression rate increased due to the black nonwoven fabric layer, and the crop yield increased by 15 to 25% compared to Comparative Example 1. In addition, in a demonstration project at the Jeju Agricultural Research and Development Administration’s Nanji Research Institute, it was confirmed that when porous mulching material was applied, sugar content increased by 1.5 to 2.9°Bx (average 1.8°Bx) compared to the untreated control, peel color a* values improved to 15.70 to 20.66, and the ratio of marketable fruit was over 90%, resulting in a 15 to 20% increase in the productivity of high-quality tangerines.
[0227] In addition, in a field demonstration of a lettuce field, it was confirmed that the yield increased by 20% compared to vinyl when using the Hybrix mulching material of the present invention, and that it is possible to harvest four times a year.
[0228] Furthermore, it was confirmed that the reduced dust adhesion allows light reflectance to be maintained for an extended period, and that the laminated structure of film and non-woven fabric results in excellent mechanical properties such as tensile strength and tear strength. Additionally, it was observed that forming perforated holes using a thermal needle method creates reinforcing rings in the perforated holes, further enhancing mechanical properties and extending the replacement cycle of the mulching material.
[0229] As seen in Comparative Examples 1 to 4, it was confirmed that the microporous hybrid mulching material according to the present invention has an overall superior effect compared to conventional mulching materials.
[0230] In addition, as seen in Comparative Example 5, it was confirmed that when graphene oxide and a compatibilizer were not included in the manufacture of the white microporous film, graphene oxide and illite were not used in the manufacture of the black nonwoven fabric, and double embossing was not formed, the overall physical properties were significantly degraded compared to Example 3. In addition, as seen in Comparative Example 6, it was confirmed that the physical properties were further degraded when perforated holes were not formed in Comparative Example 5.
[0232] As described above, the present invention has been explained by specific details and limited embodiments; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.
[0233] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention. Explanation of the symbols
[0234] 100 : Surface layer 200 : Floor 300: Adhesive layer 400 : Perforation line R1: Hole diameter L1: Hole spacing
Claims
Claim 1 A microporous hybrid mulching material comprising: a surface layer made of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer; a bottom layer made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and a black pigment; and an adhesive layer for bonding the surface layer and the bottom layer; wherein the surface layer, the adhesive layer, and the bottom layer each have a plurality of perforated holes passing through them, and the white microporous film has a double embossing structure with different diameters. Claim 2 In claim 1, the microporous hybrid mulching material, wherein the perforated holes and the bottom layer are impregnated with a hydrophilic surfactant, Claim 3 A microporous hybrid mulching material according to claim 1, wherein the perforated holes are formed by thermal needle perforation or laser perforation while the surface layer, adhesive layer, and bottom layer are laminated. Claim 4 A microporous hybrid mulching material according to claim 1, wherein the hole diameter R1 of the perforated hole is 0.1 to 0.5 mm and the spacing L1 is 1 to 5 mm. Claim 5 delete Claim 6 A microporous hybrid mulching material according to claim 1, wherein the white microporous film comprises 3 to 10 weight% of low-density polyethylene (LDPE), 30 to 50 weight% of metallocene linear low-density polyethylene (mLLDPE), 40 to 60 weight% of calcium carbonate, 0.05 to 0.2 weight% of graphene oxide, 0.5 to 5 weight% of white pigment, 0.5 to 5 weight% of pearl pigment, and 1 to 5 weight% of a compatibilizer. Claim 7 In claim 1, the white microporous film is a microporous hybrid mulching material having a thickness of 0.01 to 0.05 mm and a porosity of 10 to 50%. Claim 8 A microporous hybrid mulching material according to claim 1, wherein the black nonwoven fabric comprises 85 to 95 weight% of base resin, 0.05 to 0.2 weight% of graphene oxide, 0.1 to 10 weight% of illite, and 0.5 to 5 weight% of black pigment. Claim 9 A microporous hybrid mulching material according to claim 1, wherein the black pigment is carbon black. Claim 10 A microporous hybrid mulching material according to claim 1, wherein the black nonwoven fabric has a basis weight of 15 to 80 g / m². Claim 11 A microporous hybrid mulching material according to claim 1, wherein the black nonwoven fabric is selected from polyester-based nonwoven fabrics, polyolefin-based nonwoven fabrics, and bicomponent nonwoven fabrics thereof. Claim 12 A microporous hybrid mulching material according to claim 1, wherein the total thickness of the microporous hybrid mulching material is 0.02 to 0.1 mm. Claim 13 In claim 1, the microporous hybrid mulching material has a water vapor permeability of 500 g / m² according to ASTM F1249 or ASTM E96. 2 It is greater than 24h, and the air permeability measured according to ASTM D726 or DIN EN ISO 9237 (1995-12) is 100 L / m 2 Microporous hybrid mulching material having a value of ·s or higher. Claim 14 In claim 1, the microporous hybrid mulching material has a tensile strength of 20 N / 5 cm or more according to ASTM D5035, a tear strength of 5 N or more according to ASTM D1922, and a soil temperature change of ±2 to 3 ℃ according to ISO 9869. Claim 15 In claim 1, the microporous hybrid mulching material has a specular reflectance of 5% or less according to ASTM E1396 and a haze of 80% or more according to ASTM D1003. Claim 16 A method for manufacturing a microporous hybrid mulching material, comprising: a first step of laminating a surface layer made of a white microporous film comprising a polyolefin resin, graphene oxide, calcium carbonate, a white pigment, a pearl pigment, and a compatibilizer; and a bottom layer made of a black nonwoven fabric comprising a base resin, graphene oxide, illite, and a black pigment through an adhesive layer; and a second step of forming a plurality of perforated holes by thermal needle perforation or laser perforation while the surface layer, the adhesive layer, and the bottom layer are laminated, wherein the white microporous film has a double embossing structure having different diameters. Claim 17 A method for manufacturing a microporous hybrid mulching material according to claim 16, wherein the adhesive layer is formed by a dry lamination method using an adhesive selected from heat bonding, ultrasonic bonding, hot melt adhesive, and water-based polyurethane adhesive. Claim 18 A method for manufacturing a microporous hybrid mulching material according to claim 16, wherein the hole diameter R1 of the perforated hole is 0.1 to 0.5 mm and the spacing L1 is 1 to 5 mm. Claim 19 A method for manufacturing a microporous hybrid mulching material according to claim 16, further comprising the step of impregnating the microporous hybrid mulching material having the perforated holes formed therein with a hydrophilic surfactant, or spray-applying a hydrophilic surfactant so that the hydrophilic surfactant is impregnated into the perforated holes and the bottom layer. Claim 20 A method for manufacturing a microporous hybrid mulching material according to claim 19, further comprising the step of performing a hydrophilic treatment selected from corona treatment or plasma treatment on the surface layer of the microporous hybrid mulching material having the perforated holes formed therein before impregnating or applying the hydrophilic surfactant. Claim 21 A method for manufacturing a microporous hybrid mulching material according to claim 16, wherein the white microporous film is manufactured by: a) melt-extruding a composition comprising 3 to 10 weight% of low-density polyethylene (LDPE), 30 to 50 weight% of metallocene linear low-density polyethylene (mLLDPE), 40 to 60 weight% of calcium carbonate, 0.05 to 0.2 weight% of graphene oxide, 0.5 to 5 weight% of white pigment, 0.5 to 5 weight% of pearl pigment, and 1 to 5 weight% of a compatibilizer to produce a sheet; b) biaxially stretching the sheet to produce a microporous film; and c) forming a double embossing structure having different diameters on the surface of the microporous film. Claim 22 A method for manufacturing a microporous hybrid mulching material according to claim 16, wherein the black nonwoven fabric comprises the step of manufacturing a nonwoven fabric using a composition comprising 85 to 95 weight% of base resin, 0.05 to 0.2 weight% of graphene oxide, 0.1 to 10 weight% of illite, and 0.5 to 5 weight% of black pigment.
Citation Information
Patent Citations
Agricultural film
JP2019017360A
Antifogging agent for agricultural film
JP2024030457A
Agricultural porous laminated mulching film and manufacturing method thereof
KR1020240074958A
Manufacturing method for Anti-fugging biodegradable cleaner emitting flavor with non-slip surface
KR1020240169970A
Heat-generating funtional mulching mats containing light-heating particles
KR102574880B1
